2021
DOI: 10.1111/vsu.13621
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic and ultrasonographic examination findings in 128 shoulders of 64 ultra‐endurance Alaskan sled dogs

Abstract: Objective: To determine the location and periarticular shoulder-muscleabnormalities detected via orthopedic examinations and ultrasonography in ultra-endurance Alaskan sled-dogs, returned from an ultra-endurance sleddog-race prior to finishing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Over 80% of the dogs ultrasounded had an abnormal finding. No correlation was found between clinical signs and abnormal ultrasound findings ( 9 ). In addition, there was a wide variety of shoulder abduction angles even in normal joints and fluid around the biceps tendon could not be related to pain in the shoulder.…”
Section: Discussionmentioning
confidence: 92%
“…Over 80% of the dogs ultrasounded had an abnormal finding. No correlation was found between clinical signs and abnormal ultrasound findings ( 9 ). In addition, there was a wide variety of shoulder abduction angles even in normal joints and fluid around the biceps tendon could not be related to pain in the shoulder.…”
Section: Discussionmentioning
confidence: 92%
“…Of these, 13 were excluded: 6 due to evidence of high impact trauma (1P, 5NP), 4 due to glenohumeral dysplasia (1P, 3NP), and 3 due to potentially contributing comorbidities (3NP), leaving 61 dogs with presumed MSI, diagnosed in clinical records by a combination of abduction angle assessment, radiographs, and arthroscopic assessment. Given the limitation of diagnosis of grade 1–3 MSI based on palpation and radiographic assessment alone, 10 11 12 13 inclusion criteria required confirmation via arthroscopic examination for all grade 1–3 cases ( n = 11; 2P, 9NP) and/or radiographic evidence of medial luxation of the humeral head for grade 4 MSI ( n = 37; arthroscopic diagnosis in 18 = 7P, 11NP; radiographic diagnosis in 19 = 8P, 11NP). Lack of confirmation of diagnosis by these methods excluded a further 13 dogs.…”
Section: Resultsmentioning
confidence: 99%
“…The accepted “normal abduction angle” has been shown to be approximately 30 degrees 9 and, although past studies suggested that abduction angles could be used to diagnose MSI, it has since been shown that significant variation occurs between observers measuring abduction angles, that abduction angles do not closely correlate to arthroscopic pathology, and that abduction angles of up to 75 degrees may be observed in normal joints. 10 11 12 13 Hence a diagnosis of MSI cannot be based upon abduction angle measurement alone. In cases of instability/subluxation (MSI grade 1–3), arthroscopy is required to confirm the diagnosis; luxation (MSI grade 4) can be diagnosed from radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…This diagnostic technique has recently been proven to be not as reliable and repeatable as initially suggested. 11,12 In our study, the surgeon assessed the tension to apply on the sutures to reduce the instability. Further studies correlating the reduction of the abduction angle with the tension applied on the sutures would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of maximum abduction angle of the shoulder joint has been described to be an easily feasible diagnostic tool to assess medial shoulder laxity. 9 However, some recent studies showed that maximum shoulder abduction angles varied greatly and could reach up to 75 degrees un normal joints, questioning the reliability 11,12 and specificity 13 of this test.…”
Section: Introductionmentioning
confidence: 99%